The Effect of Using Synbiotic on Weight Loss, Body Fat Percentage and Anthropometric Measures in Obese Women - Batu, Zehra; Gök Balcı, Umut; Akal Yıldız, Emine (Progress in Nutrition, 2021)
Abstract: Objective: This is a randomly controlled, synchronously done, single-blind study which aims to in-vestigate the effects of synbiotic use on anthropometric measurements and energy intake. Materials and Meth-ods: Sixty-one not compliant with diet and exercise recommendations, sedentary obese women (BMI: 30-39.9 kg/m2 ) who fulfilled inclusion criteria, aged between 18 and 48 randomly categorized into synbiotic (n=30) or control (n=31) group. The synbiotic and control groups consumed 1 synbiotic capsule/day or 1 placebo capsule/day during 6 weeks, respectively, without changing the ongoing diet. Anthropometric measurements (body weight, body mass index, waist circumference, hip circumference, waist / hip ratio and body fat ratio) are done at the beginning, at 3 th week and at 6 thweek. Also, 24 hours of their food consumption are recorded at the be-ginning of the study and once a week during the study. Results: Repeated measurements of body weight, body fat ratio, waist circumference, hip circumference, and the calculations of body mass index and waist/hip ratio are analyzed with mixed effect linear model and therefore, the interaction terms with group and time effects are not found significantly (p> 0.05). No difference (increase or decrease) are observed in energy intake of participants in two groups at the beginning and during the study (p> 0.05). Conclusion: Synbiotic supplement did not change antropometric measures, body composition and daily energy intake in not compliant with diet and exercise recommendations obese women. Further studies are needed to indicate the effects of synbiotic use in obesity treatment.